AC Loss Evaluation of a Superconducting Pancake Coil with Coated Conductors using an Extended A-V Formulation - Inanir, Fedai; Terzioglu, Rifki (ELSEVIER, 2021)
In this study, an extended A-V formulation is used to determine the alternating current (AC) losses of a coil made of high temperature superconducting (HTS) tape. The current is the same at each turn by balancing the voltages of each turn. By this modification, this method can be applied in a wide application area. This method also provides the chance to determine the calculations at currents higher than the critical current values in a more stable way. The AC loss characteristics of the pancake coil are examined in detail by changing the current value and frequency. Also, the losses at individual turns (1st, 5th, and 10th) are presented. It was seen that the most outer and inner turns have higher losses than that of the other turns. The AC loss results obtained from the extended A-V formulation used in this study are compared with experimental and H-formulation-based results and are in good agreement. The frequency dependence of the pancake coil's loss is revealed at 5 frequency values. The results show that the loss is frequency and current amplitude dependent as expected. Similarly, the calculated losses for each frequency are in good agreement with that obtained from the H-formulation. The current distributions of a single tape and the entire coil are also presented, and all results are discussed in detail.
Keywords: A-V formulation; H-formulation; AC loss; Pancake Coil; CRITICAL-STATE; CARRYING AC; Physics